Memperjelas Variasi Bahasa Melalui Faktor Sosial dalam Percakapan Pemeran Tokoh di Media Webseries “Imperfect The Series S2 Episode 1-5”: Perspektif Sosiolinguistik - Bhrata, Pramudya Dhana; Yustanto, Henry; Yulianti, Wiwik (Jurnal Ilmiah Dikdaya, 2024)
This paper aims to describe research information regarding language variations through socialfactors in the conversations of characters in the media webseries "Imperfect The Series S2 Episode 1-5":Sociolinguistic Perspective with analysis of the variety of language and speech that appears by the characters ofthe webseries "Imperfect The Seri S2 Episodes 1-5”. This research uses a qualitative descriptive approachbecause the data taken is in the form of written and unwritten word/sentence data. This qualitative researchmethod is used to help understand the social factors that influence the emergence of language variations in thelanguage used in each communication by the characters in the webseries "Imperfect The Series S2 Episode 1-5". The data collected in this research is descriptive data in the form of words/sentences of characters'conversations in the webseries "Imperfect The Series S2 Episode 1-5" using data transcription of the characters'utterances which contain variations/variety of language. The data source for this research comes from theWebseries "Imperfect The Series S2 Episode 1-5". Other supporting sources in this research are journals andarticles that are relevant to this research. In this research, the data collection techniques used include FreeListening Free Cakap (SBLC), katat techniques, and content analysis. The use of these techniques was chosenbecause it is in accordance with the research focus which relates to oral data that has been transliterated. Thedata analysis technique in this research was carried out through three stages, namely the first stage of datareduction, the second stage of data presentation, the third drawing conclusions. The results of this researchshow that there are variations in language in the utterances/utterances of each conversation in the role ofcharacters in the media webseries "Imperfect The Series S2 Episode 1-5" which is influenced by social factors.It can be concluded that in the research results there are 54 forms of language variations used by the charactersin the web series "Imperfect The Series S2 Episode 1-5". Of the 54 data, 22 data are forms of funnymispronunciations, 12 data are forms of language/abbreviated words, 5 data are shortened forms, and 2 dataare forms of interjections.